STRATEGI PEMBELAJAR INDONESIA MENGIDENTIFIKASI MAKNA KATA BAHASA ARAB DALAM KONTEKS KALIMAT WACANA GEOGRAFI - Asrori, Imam (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2016)
This restrospective research studied the strategies employed by Indonesian students in identifiying the meaning of Arabic words in context. This study found: first, the students identified the word meaning using the following strategies: (a) using a billingual dictionaries (digital dictionary, printed dictionary, online dictionary), (b) asking friends, and (c) utilizing context. Second, students were able to identify the full context and identify the meaning of difficult words accurately. Third, relating meaningful context and accurate meaning which found four patterns of integrating context and accuracy of meaning, namely (a) full context and accurate meaning (F-A), (b) full context but innacurate meaning (F-NA), (c) incomplete context but accurate meaning ( NF-A), and (d) incomplete context and inacurate meaning (NF-NA). The ability to identify full context tends to help students to identify the meaning of words accurately.DOI: 10.24865/ajas.v1i2.4